World Development Indicators 2005 - World Bank (Washington, DC: World Bank, 2013)
Five years ago the Millennium Declaration recorded the commitment of the members of the United Nations to eliminate poverty and to build a secure and peaceful world conducive to human development. The Millennium Development Goals (MDGs) embocdy that commitment and set quantified targets for reducing poverty and hunger, educating all children, empowering of women, combating disease and reducing premature deaths, ensuring environmental sustainability, and establishing and effective partnership between countries and developing countries. These goals have become widely accepted as a framework for measuring development progress. Since the articulation of the MDGs, World Development Indicators has reported on progress toward each goal. This year's edition provides a more comprehensive survey on the main targets and indicators. The report includes, more than 800 indicators from 153 economies, provides definitions, sources and other information about the data, the data is organized into six thematic areas : People (gender, health and employment); Environment (natural resources and environmental changes); World view (progress towards the MDGs); Economy (new opportunities for growth); Global links (evidence of globalization); and States and Markets (elements of a good investment climate). Improvement in global statistics requires a continued effort of many partners. A good example is the work of the UN's interagency and expert group on the MDGs. By bringing together the many agencies responsible for comprising indicators used to monitor progress towards, the MDGs, the Group has created and important forum for identifying statistical gaps, harmonizing work, and disseminating reliable indicators. The results of their activities are visible in the report on the MDGs in the World view section and throughout the rest of this book.